THY KINGDOM COME? MISSION AS RECEPTION FOR REDEEMING EVANGELISM IN THE CHURCH OF ENGLAND. Issue 3 (July 2019) - Percy, Martyn
Abstract : The Church of England Report Faith in the City represented a theology rooted in the Kingdom of God, giving priority to people and the places they lived in over the needs of the church. But now we are in the age of the Mission-Shaped Church, and in danger of letting the growth of the institutional church take priority. This article argues that a liberal theology of evangelism must begin in listening, rather than broadcast, mode, and have the courage both to learn from those around us, and to be still.